Elizabethan and Jacobean lute manuscripts: types, characteristics and compilation - Craig-McFeely, J (Cairn, 2021)
This study examines English manuscripts of music for solo lute from between 1570 and 1630, the period when solo lute music in England enjoyed its brief but most eloquent flowering. Biographical information regarding owners, together with the codicology of the compilations, makes it possible to define the characteristics of different types of usage. This enables a modern reader to understand the contents of the books in their socio-cultural context, as windows into both personal tastes and wider musical practices. Understanding the purpose of these books provides clues to practices such as the contemporary preservation of ephemera, lute lessons and the activities of professional copyists. The broad characteristics of each type of usage are described, with reference to some of the most notable exemplars.